Thalassemia, a human blood disorder - Shafique,F. (2023)
Abstract A group of inherited blood defects is known as Thalassemia is among the world’s most prevalent hemoglobinopathies. Thalassemias are of two types such as Alpha and Beta Thalassemia. The cause of these defects is gene mutations leading to low levels and/or malfunctioning α and β globin proteins, respectively. In some cases, one of these proteins may be completely absent. α and β globin chains form a globin fold or pocket for heme (Fe++) attachment to carry oxygen. Genes for alpha and beta-globin proteins are present in the form of a cluster on chromosome 16 and 11, respectively. Different globin genes are used at different stages in the life course. During embryonic and fetal developmental stages, γ globin proteins partner with α globin and are later replaced by β globin protein. Globin chain imbalances result in hemolysis and impede erythropoiesis. Individuals showing mild symptoms include carriers of alpha thalassemia or the people bearing alpha or beta-thalassemia trait. Alpha thalassemia causes conditions like hemolytic anemia or fatal hydrops fetalis depending upon the severity of the disease. Beta thalassemia major results in hemolytic anemia, growth retardation, and skeletal aberrations in early childhood. Children affected by this disorder need regular blood transfusions throughout their lives. Patients that depend on blood transfusion usually develop iron overload that causes other complications in the body systems like renal or hepatic impairment therefore, thalassemias are now categorized as a syndrome. The only cure for Thalassemias would be a bone marrow transplant, or gene therapy with currently no significant success rate. A thorough understanding of the molecular basis of this syndrome may provide novel insights and ideas for its treatment, as scientists have still been unable to find a permanent cure for this deadly disease after more than 87 years since it is first described in 1925.